Ceramaster patagonicus Sladen 1889 ... - Mah, Christopher L. (Zenodo, 2011)
Ceramaster patagonicus (Sladen, 1889) (Figure 2 A–G) Sladen, 1889: 269, pl. 46, figs 3–4, pl. 44, figs 3–4. (as Pentagonaster patagonicus) Perrier, 1891: K127, pl. 12, figs 3a–b (as Pentagonaster austrogranularis) Verrill, 1899: 195 (as Mediaster patagonicus) Verrill, 1899: 195 (as Pseudarchaster patagonicus) Fisher, 1911: 214, pl. 37, fig. 4,, pl. 38, figs 1–2, pl. 40, fig. 3; 1940: 118; Djakonov, 1950: 48, figs. 27, 48; Bernasconi, 1963: 8, pl. 1, figs. 1–2, pl.2, fig. 3; Baranova & Belyaev 1968: pl. 17, fig. 2; Tommasi, 1970: 12, fig. 36; Lambert, 1978: 62; Anderson et al., 1993: 502; Branch et al., 1993: 44 (illustr.); A.M. Clark, 1993: 249; Rowe & Gates, 1995: 65; O’Hara, 1998: 179, pl. 1d.; H.E.S. Clark in Clark & McKnight, 2001: 33; Stampanato & Jangoux, 2004: 4, 6 (as Ceramaster patagonicus) McKnight, 1973: 178, fig. 4; 1984: 142; A.M. Clark, 1993: 249 (as Ceramaster lennoxkingi) Clark & Downey, 1992: 236 (as Ceramaster grenadensis patagonicus) Range. Broadly distributed. Bering ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on pages 8-10, DOI: 10.5281/zenodo.276783 ...